Analysis of Computer Code and Method Used in Thermal-Hydraulic Safety Justification of VVER Reactor Plants - Stepan Lys (Energy Engineering and Control Systems, 2022)
This article presents the analysis of the calculation procedure and computer code KLAST used in calculations of the control rod dynamic characteristics during safety justification of water-cooled water-moderated power reactor plants. The code allows accounting for pressure differentials as a function of time occurred under the design conditions on the reactor core and on the drive extension shaft as well change of coolant density in the core. The code can be used to calculate dynamic characteristics of the control and protection system of control rod of VVER-1000 reactor types under the design accident conditions with rupture of the drive housing and to calculate the control and protection system of control rod dynamic characteristics during drop and damping in case of reactor damage during design accident conditions with pipeline break. In calculation, the control and protection system of control rod dynamic characteristics are determined versus time.